An evaluation of the safety and efficacy of a variable rate intravenous insulin infusion in the management of hyperglycaemia in acute coronary syndrome: experience of the TITAN-ACS - Clive Weston (British Journal of Diabetes, 2015)
Aim. To assess the safety and efficacy of a variable rate intravenous insulin infusion to lower blood glucose (BG) in patients presenting with acute coronary syndrome and hyperglycaemia.Methods. We evaluated the response over 24 hours of a variable rate insulin infusion with 5% dextrose and potassium chloride (40 mEq/l), to control hyperglycaemia in 776 patients with an admission BG  10 mmol/l in 36 UK hospitals. Patients had either ST segment elevation or non-ST segment elevation myocardial infarction and the study included both patients with or without a diagnosis of diabetes. We measured blood glucose, initially hourly, and serum potassium at admission, and 24 hours and at the time of major arrhythmias. We measured survival to 30 days.Results. Median admission BG was 13.4 mmol/l (interquartile range 11.7, 18). At 6 hours BG was 8.0 mmol/l (6.2, 10.8), and at 20-24 hours was 8.3 mmol/l (6.5, 11.0). Hypokalaemia due to the infusion was not observed. Hypoglycaemia (BG <3 mmol/l) occurred in 4.1% patients, and most frequently (8.6%) in the lowest weight quartile, adjusted odds ratio 3.91, p=0.008. 30-day survival was not adversely affected by the occurrence of hypoglycaemia. Patients in the highest weight quartile were more likely to have glucose in the upper quartile, >10.8 mmol/l at 6 hours; adjusted odds ratio 1.82, p=0.011. Conclusions. This insulin regimen was safe and effective with low rates of hypoglycaemia and no excess mortality in the hypoglycaemic sub-group. Further adjustments are required for those in the lowest and highest quartiles of weight.